Is Competency-Based Medical Education being implemented as intended? Early lessons learned from Physical Medicine and Rehabilitation - Trier, Jessica; Askari, Sussan; Hanmore, Tessa; Thompson, Heather-Ann; McGuire, Natalie; Braund, Heather; Hall, Andrew Koch; McEwen, Laura; Dalgarno, Nancy; Dagnone, Jeffrey Damon (Canadian Medical Education Journal, 2024)
Background: As competency-based medical education (CBME) curricula are introduced in residency programs across Canada, systematic evaluation efforts are needed to ensure fidelity of implementation. This study evaluated early outcomes of CBME implementation in one Canadian Physical Medicine and Rehabilitation program that was an early adopter of CBME, with an aim to inform continuous quality improvement initiatives and CBME implementation nationwide. Methods: Using Rapid Evaluation methodology, informed by the CBME Core Components Framework, the intended outcomes of CBME were compared to actual outcomes. Results: Results suggested that a culture of feedback and coaching already existed in this program prior to CBME implementation, yet faculty felt that CBME added a framework to support feedback. The small program size was valuable in fostering strong relationships and individualized learning. However, participants expressed concerns about CBME fostering a reductionist approach to the development of competence. Challenges existed with direct observation, clear expectations for off-service training experiences, and tracking trainee progress. There was trepidation surrounding national curricular change, yet the institution-wide approach to CBME implementation created shared experiences and a community of practice. Conclusions: Program evaluation can help understand gaps between planned versus enacted implementation of CBME, and foster adaptations to improve the fidelity of implementation.